Distribution, growth, and structure of pine-beech forest stands in the Lviv Roztochchia region - Hryhoriy Krynytskyy; Lubomyr-Olexandr Debryniuk; Valentyna Kovaleva; Mykola Korol; Volodymyr Kramarets; Olga Krynytska; Roman Kuziv; Vasyl Lavnyy; Natalia Lutsiv; Stepan Myklush; Ihor Skolskyy; Volodymyr Yakhnytsky (Наукові праці Лісівничої академії наук України)
In the western part of Ukraine, pine-beech forest stands are widespread only in the physico-geographical regions of Roztochchia and Opillia. Their total area is 8,204.5 hectares, of which 6,246.5 hectares (76.13%) are occupied by stands of natural origin, 1,890.8 hectares (23.05%) are forest plantations, 5.5 hectares (0.07%) are sparse forests, 20.0 hectares (0.24%) are naturally occurring stands with admixture of forest cultures, 41.2 hectares (0.50%) are unclosed forest cultures, and 0.5 hectares (0.01%) are forest nurseries.